The Influence of Consumer Motivation, Perception of Quality And Consumer Attitude Towards Buying Decision at PT. Unikitz United Group Medan - Desma Erica M Manik; Irvan Rolyesh Situmorang; Muammar Rinaldi (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
ABSTRACT This study aims to determine the effect of consumer motivation, perceived quality and consumer attitudes on purchasing decisions at PT. Unikitz Bersatu Group Medan branch. The population in this study are all stores that have made purchases at PT. Unikitz Bersatu Group Medan branch for the 2019 period. The research population that will be used in the study is all consumers who made purchases at the company in 2019 as many as 12,139 consumers. By using the Slovin formula with an error rate of 5%, the number of samples obtained is 99 respondents. The results of the research analysis show that Consumer Motivation, Quality Perception and Consumer Attitude partially and simultaneously have a positive and significant effect on Purchase Decisions at PT. Unikitz Bersatu Group Medan branch. The results of this study are supported by the value of Adjusted R square (Adjusted R2), which means that consumer motivation, perceived quality and consumer attitudes have an influence on purchasing decisions at PT. Unikitz Bersatu Group Medan branch. While the rest is influenced by other factors that come from outside this research model such as consumer behavior, service quality, product quality, product design and various other variables.